ICTs in Namibia's communal area conservancies - Murphy, Carol; Slater-Jones, Sandra (Technical Centre for Agricultural and Rural Cooperation, 2005)
Carol Murphy and Sandra Slater-Jones describe a GIS mapping procedure in which local people, and not outsiders, are the experts.